THE STATE OF METABOLISM OF BILIRUBIN IN DOMESTIC DOGS AND CATS AT HEPATITIS - Локес, П. І.; Кравченко, С. О.; Локес-Крупка, Т. П. (Scientific Progress & Innovations, 2014)
It was found that in dogs and cats with hepatitis pigment function of liver is disturbed. There is a violation of dynamic equilibrium between formation, conjugation and excretion of bilirubin. In dogs with acute hepatitis the number of total bilirubin increased to 5.0, conjugated - at 13.1 times; more disturbed allocation of conjugated form of pigment. In cats, the content of total bilirubin increased to 10.5 times and equally disturbed synthesis dyglucuronide of bilirubin and its excretion.